Kewajiban Pembayaran Pesangon Kepada Karyawan Usia Pensiun Yang Terkena Pemutusan Hubungan Kerja Sepihak - Felicia Felicia; Gunardi Gunardi (UNES Law Review, 2023)
Companies often terminate employment relationships with their employees because the company’s conditions are not good, employees have reached their retirement age, etc. After terminating an employment relationship, employers are required to pay severance pay to employees as regulated in the employment law. However, there are still many companies that do not pay the severance pay or even only pay half of the severance pay which should disappoint their employees. This research aims to find out what the regulations regarding the rights and obligations of the parties are based on labor law. This research uses a normative research method using a statutory and regulatory approach related to this research and a case apporach in the Pontianak District Court Decision Number 25/Pdt.Sus-PHI/2021/PN.Ptk. Based on the research that has been carried out, employers have violated Article 156 of Law Number 13 of 2003 concerning Employment and are required to pay the severance pay after terminating their employment. The conclusion of this writing is that it is hoped for the employees and employers will comply with the rights and obligations that have been agreed before starting the employment relationship, including the agreement on severance pay so that conflict cannot be occur and the welfare of the parties can be achieved.